Cardioprotective Role of Myeloid-Derived Suppressor Cells in Heart Failure. Issue 2 (10th July 2018) - Zhou, Ling; Miao, Kun; Yin, Bingjiao; Li, Huaping; Fan, Jiahui; Zhu, Yazhen; Ba, Hongping; Zhang, Zunyue; Chen, Fang; Wang, Jing; Zhao, Chunxia; Li, Zhuoya; et al.
Abstract : Background: Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of cells that expand in cancer, inflammation, and infection and negatively regulate inflammation and the immune response. Heart failure (HF) is a complex clinical syndrome wherein inflammation induction and incomplete resolution can potentially contribute to HF development and progression. However, the role of MDSCs in HF remains unclear. Methods: The percentage of MDSCs in patients with HF and in mice with pressure overload–induced HF using isoproterenol infusion or transverse aortic constriction (TAC) was detected by flow cytometry. The effects of MDSCs on isoproterenol- or TAC-induced HF were observed on depleting MDSCs with 5-fluorouracil (50 mg/kg) or gemcitabine (120 mg/kg), transferring purified MDSCs, or enhancing endogenous MDSCs with rapamycin (2 mg·kg −1 ·d −1 ). Hypertrophic markers and inflammatory factors were detected by ELISA, real-time polymerase chain reaction, or Western blot. Cardiac functions were determined by echocardiography and hemodynamic analysis. Results: The percentage of human leukocyte antigen-D–related (HLA-DR) − CD33 + CD11b + MDSCs in the blood of patients with HF was significantly increased and positively correlated with disease severity and increased plasma levels of cytokines, including interleukin-6, interleukin-10, and transforming growth factor–β. Furthermore, MDSCs derived from patients with HF inhibited T-cell proliferation and interferon-γ secretion. Similar results were observed in TAC- and isoproterenol-induced HF in mice. Pharmaceutical depletion of MDSCs significantly exacerbated isoproterenol- and TAC-induced pathological cardiac remodeling and inflammation, whereas adoptive transfer of MDSCs prominently rescued isoproterenol- and TAC-induced HF. Consistently, administration of rapamycin significantly increased endogenous MDSCs by suppressing their differentiation and improved isoproterenol- and TAC-induced HF, but MDSC depletion mostly blocked beneficial rapamycin-mediated effects. Mechanistically, MDSC-secreted molecules suppressed isoproterenol-induced hypertrophy and proinflammatory gene expression in cardiomyocytes in a coculture system. Neutralization of interleukin-10 blunted both monocytic MDSC- and granulocytic MDSC–mediated anti-inflammatory and antihypertrophic effects, but treatment with a nitric oxide inhibitor only partially blocked the antihypertrophic effect of monocytic MDSCs. Conclusions: Our findings revealed a cardioprotective role of MDSCs in HF by their antihypertrophic effects on cardiomyocytes and anti-inflammatory effects through interleukin-10 and nitric oxide. Pharmacological targeting of MDSCs by rapamycin constitutes a promising therapeutic strategy for HF. Abstract : Supplemental Digital Content is available in the text.